PENGUATAN KECERDASAN SPIRITUAL MELALUI KEGIATAN KEAGAMAAN BERBASIS FUN LEARNING - Alya Rekha Anjani; Acep Mulyadi; Akmal R Gunawan Hasibuan (Al-Ihsan: Journal of Community Development in Islamic Studies, 2022)
Students are not only required to have a high IQ or intellectual quotients. However, students must also be able to balance intellectual intelligence with emotional quotients or EQ and spiritual quotients or SQ. Moreover, during the on going pandemic, students experience a decadence in spiritual intelligence because they are busy with their gadgets and lack of religious activities in their home environment. The purpose of this community service is to strengthen the spirituality of the teenagers in the community Villa Mutiara Jaya RT. 007 RW. 037 through fun learning-based religious activities, such as learned tajwid with song, watched Islamic movie, and played Islamic education game online (use Wordwall and Quizziz game). The Methode used in the implementation of this program is public education. The results of this activities is that teenagers can be more enthusiastic about learning and participating in religious activities then their spiritual intelligence becomes stronger than before.